KONSEP ITIKAD BAIK DALAM PENERAPAN BUSINESS JUDGMENT RULE BERDASARKAN SISTEM HUKUM PERSEROAN INDONESIA DAN MALAYSIA - Bewani Octavianisa Masrurah (Mandala, 2019)
The Business Judgment Rule doctrine can protect directors from their responsibilities in making decisions for the company. Furthermore, it raises the question, how is the concept of good faith based on the Business Judgment Rule doctrine in Indonesia, and for that it is also compared to its application in Malaysia. This study aims to understand the concept of good faith that is always included in the application of Business Judgment Rules in the Indonesian legal system and how it is applied in Malaysia. This research is a normative research with a legislative approach and a conceptual approach both applicable in Indonesia and Malaysia. From the results of this study indicate that there are differences in the application of the concept of good faith in the Business Judgment Rule in Indonesia and Malaysia, one of which is the Companies Act of Malaysia clearly and completely stated about good faith for directors, while in Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas is not explained clearly and in detail.